2021
DOI: 10.18632/oncotarget.27909
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of somatic mutations in breast cancer: new opportunities for targeted therapies in Saudi Arabian patients

Abstract: Breast cancer (BCa) ranks first in incidence rate among cancers in Arab females. The association between genetic polymorphisms in tumor suppressor genes and the risk of BCa has been studied in many ethnic populations with conflicting conclusions while Arab females and Saudi Arabian studies are still lacking. We screened a cohort of Saudi BCa patients by NGS using a bespoke gene panel to clarify the genetic landscape of this population, correlating and assessing genetic findings with clinical outcomes. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Such patients will benefit from reassessing their tumors for a better targeted therapy (see examples in Figure 4 ). We propose the routine use of CGP for brain metastasis patients similar to that described in our previous studies ( 18 , 19 , 41 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Such patients will benefit from reassessing their tumors for a better targeted therapy (see examples in Figure 4 ). We propose the routine use of CGP for brain metastasis patients similar to that described in our previous studies ( 18 , 19 , 41 ).…”
Section: Discussionmentioning
confidence: 77%
“…Previous literature has highlighted the need to explore the PI3K/AKT/mTOR pathway in aggressive tumors ( 19 ), and this includes brain metastatic tumors and their primary counterparts, suggesting the PI3K/AKT/mTOR pathway as a potential therapy target to prevent brain metastasis formation ( 20 , 21 ). PI3K/AKT/mTOR inhibitory agents that have been studied in literature, such as rapamycin and everolimus, which both inhibit mTOR, are expected to lead to better therapeutic responses compared to traditional treatment modalities in primary breast cancers ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these results needs to be based on data from more clinical samples. Studies have shown that PIK3CA and HRAS are prone to a mutation in a variety of tumors, resulting in their persistent hyperactivity, which promotes cancer cell proliferation and migration [39,40]. Therefore, this study analyzed 9536 BC samples from 18 studies via the cBioPortal database, and the results showed that the mutation rate of PIK3CA was 36%, while that of HRAS was only 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these results needs to be based on data from more clinical samples. Studies have shown that PIK3CA and HRAS are prone to a mutation in a variety of tumors, resulting in their persistent hyperactivity, which promotes cancer cell proliferation and migration [ 42 , 43 ]. Therefore, this study analyzed 9536 BC samples from 18 studies via the cBioPortal database, and the results showed that the mutation rate of PIK3CA was 36%, while that of HRAS was only 1.1%.…”
Section: Discussionmentioning
confidence: 99%